Effects of Etlingera elatior inflorescence extract on beneficial bacteria of the healthy human gut - Kavithra, (Journal of Biomedical Sciences, 2021)
Background: Etlingera species is an enduring plant in the Zingiberaceae family, with more than 100 species local to many countries. It has been utilized commonly as a culinary spice or eaten crude for its therapeutic impacts. This research is intended to study the effects of E. elatior inflorescence, which is commonly known as bunga kantan in Peninsular Malaysia, upon the microbiota of healthy human gut. Material and methods: The closed bud E. elatior inflorescence was cleaned and dried in the hot air oven and grounded into fine powder. The extract from the E. elatior inflorescence was obtained using hot water extraction method. The effects of the inflorescence extract on L. rhamnosus and L. acidophilus were studied through micro-broth dilution process where different concentration of sample was incorporated into a broth medium followed by the application of a standardized volume of Lactobacillus sp. into the medium of the 96 well plate. Results: Growth was seen in both L. rhamnosus and L. acidophilus, indicating that E. elatior inflorescence acted like a prebiotic towards L. acidophilus and L. rhamnosus Conclusion: E. elatior inflorescence concentrate acts like a prebiotic towards L. acidophilus incomparable to L. rhamnosus